1981
DOI: 10.1136/bmj.283.6302.1287
|View full text |Cite
|
Sign up to set email alerts
|

DR antigens and rheumatoid arthritis: a study of two populations.

Abstract: inexpensive and provides a new technique for the diagnosis of non-immunologically mediated bronchial hyperreactivity. DR antigens and rheumatoid arthritis: a study of two populationsThe prevalence of HLA-DR antigens was determined in a group of white patients with rheumatoid arthritis, similar patients originating from the Indian subcontinent, and corresponding controls. Rheumatoid arthritis was found to be highly associated with DR4 in the white patients but with DR1 in the Indian patients. These results rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 7 publications
4
32
0
1
Order By: Relevance
“…As discussed, in some studies DRI has been associated weakly with a risk of RA (10)(11)(12)(13)(14). Are epitopes found in common between DR4 subtypes and DRl alleles?…”
Section: Risk For Pemphigus Vulgaris May Be Due To a Third Hypervariamentioning
confidence: 99%
“…As discussed, in some studies DRI has been associated weakly with a risk of RA (10)(11)(12)(13)(14). Are epitopes found in common between DR4 subtypes and DRl alleles?…”
Section: Risk For Pemphigus Vulgaris May Be Due To a Third Hypervariamentioning
confidence: 99%
“…Studies have shown a strong association between the disease and HLA-DR antigens in different ethnic groups: DR4 in Caucasian, American black, and Japanese patients with RA, DRl in Asian Indian and Ashkenazi Jewish patients, and Dw16 in Yakima Indians (1)(2)(3). The association is not complete, and 2630% of Caucasian patients do not carry DR4.…”
mentioning
confidence: 99%
“…Rheumatoid factors are autoantibodies that are directed against the Fc fragment of IgG. Cellular immunity is also thought to be important because of the linkage of RA to certain MHC-encoded T cell restriction elements (e.g., DR4 and DR1 [3,4]). Examination of RA synovial tissue shows high levels of proinflammatory cytokines IL-1 (5), TNF-␣ (6-8), and growth factors such as GM-CSF (7) and M-CSF (8), but the T cell-derived mediators IL-2 (8), , , and TNF-␤ (10) are either absent or present at low levels.…”
Section: Introductionmentioning
confidence: 99%